Conceiving of Contraception: World Society, Cultural Resistance, and Contraceptive Use, 1970–2012. (25th August 2020) - Cole, Wade M; Geist, Claudia
Abstract: Taking world society theory as our point of departure, we examine the effect of world culture on contraceptive use rates around the world. World-cultural rhetoric frames contraception as a necessity for economic development, a human rights issue, and a women's health matter. Using data on contraceptive use among married women for a sample of 159 countries over the period from 1970 to 2012, we find that linkages to all three sets of discourses are associated with increased use of modern contraceptive methods, over and above countries' sociocultural and economic characteristics. Nevertheless, we also find that world society influences vary across major cultural zones, defined in terms of predominant religions and geographic regions. World cultural effects are strongest in Orthodox Christian, Hindu, non-Western Protestant, and sub-Saharan African countries. There is no effect in Western and East Asian countries, where contraceptive use is comparatively high, or in zones such as non-Western Catholic nations, where the unmet need for contraception is often greatest. Compared to development and women's rights rhetoric, health-based frames appear to have the broadest and most effective reach across cultural divides. Overall, however, we find that world society processes tend to produce cross-cultural convergence in contraceptive use rates.